Synergistic effect and water dispersible tablet of propamidine and flusilazole against Botrytis cinerea - Wang, Yong; Qiao, Yonghui; Xu, Guanyou; Liu, Xiaoxiao; Ma, Zhiqing; Feng, Juntao; Chen, Guangyou (Plant disease, 2025)
Propamidine exhibited potent fungicidal activity against Botrytis cinerea, and it has no cross resistance with other commercial fungicides. In this work, propamidine and flusilazole were combined to obtain synergistic effects against gray mold and delay the development of fungicide resistance. The results suggested that the optimal synergistic ratio (SR) of propamidine to flusilazole was 4:1, with a SR of 2.07. Based on this ratio, the optimized formulation of 50% Pro · Flu (4:1) water dispersible tablet (WDT) comprised 40% propamidine, 10% flusilazole, 4% BSA, 8% benzalkonium chloride, 7% glucose, and sufficient silica to achieve a total of 100%. The WDT met the standards for active ingredient (a.i.) content, suspension rate, disintegration time, heat stability, and other relevant indicators. Importantly, the WDT at 200 μg/mL displayed over 80% preventive and curative activity, which was comparable to that of propamidine or flusilazole at 400 μg/mL in controlling gray mold. In field trials, the efficacy of WDT was significantly higher than that of the single fungicide at the equivalent dosage. This formulation could dramatically reduce the dosage of flusilazole, alleviate the pressure of screening pathogenic fungi and the risk of plant pathogens developing resistance to fungicides, ultimately decreasing the total use of pesticides and environmental pollution.